Nitrogen and Sulphur Foliar Fertilisation - Bruwer, F.A.; du Toit, W.; Buica, A. (South African Journal of Enology and Viticulture, 2019)
The effects of fertilisation can reverberate from grapes through to wines. In wine, non-volatile compounds mainly influence the taste and flavour of wines, while volatile compounds play an important role in the aromatic expression. This review includes information on the presence of non-volatile and volatile compounds reportedly affected by nitrogen and sulphure foliar fertilisation, (bio)synthesis, and evolution throughout winemaking, their chemical properties, and their implications. The second part presents the status of the research on elucidating the influence and contribution of foliar fertilisation practices on the chemical compounds throughout winemaking, from the grape to the wine.